2004
DOI: 10.1590/s0066-782x2004001800006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da dosagem direta do colesterol-LDL em amostras de sangue de 10.664 pacientes em comparação com o uso da fórmula de Friedewald

Abstract: ObjectiveTo compare direct measurement of LDL-cholesterol (LDL-C) determined by a homogeneous method with LDL-cholesterol estimation determined by the Friedewald formula in a large heterogeneous population. Methods The measurements of total cholesterol (TC) and triglycerides (TG) were performed using traditional enzymatic methods. The measurements of HDL-C and LDL-C were performed using direct methods with no precipitation, and the estimation of the LDL-C fraction was calculated using the Friedewald formula.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 21 publications
(8 reference statements)
1
9
0
3
Order By: Relevance
“…Similar results were shown by Charuruks and Milintagas [19], who indicated the direct measurement of LDL-c when TG ≥ 200 mg/dL because they found that the direct method was more precise and accurate than FF, even for TG levels between 200 and 399 mg/dL. One Brazilian study showed a similar conclusion for FF use [20]. Nevertheless, these findings do not align with those of our study, in which the LDL-c value was estimated with precision by the FF for any value of TG < 400 mg/dL.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were shown by Charuruks and Milintagas [19], who indicated the direct measurement of LDL-c when TG ≥ 200 mg/dL because they found that the direct method was more precise and accurate than FF, even for TG levels between 200 and 399 mg/dL. One Brazilian study showed a similar conclusion for FF use [20]. Nevertheless, these findings do not align with those of our study, in which the LDL-c value was estimated with precision by the FF for any value of TG < 400 mg/dL.…”
Section: Discussionsupporting
confidence: 81%
“…In the formula, the concentration of very low-density lipoproteins (VLDL) is estimated as 20% of total TG concentrations [4]. However, the particles found in patients with hypertriglyceridemia are usually a heterogeneous mixture of chylomicron remnants, VLDL, and VLDL remnants [19]. It is well known that the ratio of TG to cholesterol (TG/cholesterol) varies a lot within these particles.…”
Section: Discussionmentioning
confidence: 99%
“…At present, plasma apolipoprotein A-I and B levels have been described as better predictors of atherosclerotic diseases than lipid and lipoprotein concentrations 6,13 ; it has also been suggested that the apo B/apo A-I ratio represents a superior parameter for predicting cardiovascular risk as compared with other lipid ratios, such as total cholesterol/HDLc, LDLc/HDLc and non-HDL cholesterol/HDLc 14,15 . [20][21][22] .…”
mentioning
confidence: 99%